PERSOALAN KETERLIBATAN ORANG ASING DALAM SISTEM ADVOKASI NASIONAL DI INDONESIA DAN DI BEBERAPA NEGARA LAIN - Oleg Orlov (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2022)
The process of research of the issue regarding involvement of foreigners in the provision of legal services in each country is related to research on the national law applicable in that country and international legal norms as well. In this article, the questions mentioned above will be considered based on the laws of the Republic of Indonesia in compare with several other countries regarding advocacy as legal assistance institution including the issue of the status of advocates, their rights and obligations, differences between the status of advocates and foreign advocates, rights and obligations of foreign advocates, involvement of foreign lawyers in litigation processes, law enforcement, their role as members of legal association or association of professional experts and various other issues. Because this article is a short and preliminary study, it is not possible to make full and complex research related to this question, but the purpose of this research is to provide an overview of the legal perspectives regarding the involvement of foreigners in national advocacy compared with some other countries and to show the similarities and differences with the same legal regulations presented in Indonesian Law. The legal position prevailing in other countries can serve as the basis for the following research which explores the subject matter from a theoretical point of view and, as a practical goal, progressive things from the legal experience of other countries can serve as a starting point for perfecting national legislation in the future.